2004
DOI: 10.1177/104063870401600416
|View full text |Cite
|
Sign up to set email alerts
|

Lolitrem B Residue in Fat Tissues of Cattle Consuming Endophyte-Infected Perennial Ryegrass Straw

Abstract: Lolitrems are neurotoxins found in endophyte-infected perennial ryegrass. Lolitrems, primarily lolitrem B, are the causative agents of ryegrass staggers in livestock. To guarantee the safety of meat produced from cattle consuming endophyte-infected perennial ryegrass, lolitrem B concentrations in tissues of Japanese Black cattle were determined using high-performance liquid chromatography. Lolitrem B was not detected in muscle, liver, kidney, or cerebrum of a Japanese Black cow with signs of ryegrass staggers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 7 publications
3
26
0
1
Order By: Relevance
“…Cases of PRGS have been reported in cattle, sheep, deer, alpaca and horses (Cunningham and Hartley 1959;Mackintosh et al 1982;Holmes et al 1999). Extensive research on PRGS has been performed in ruminants and demonstrates that ingestion of lolitrem B at levels >2 ppm causes signs of neuromuscular dysfunction, which include fine tremors, ataxia, truncal sway, hyperaesthesia, tetany and cerebellar fits, and are intensified by stress or exercise (Cunningham and Hartley 1959;Mackintosh et al 1982;Galey et al 1991;Di Menna et al 1992;Tor-Agbidye et al 2001;Fisher et al 2004;Miyazaki et al 2004;Blythe et al 2007). No effective treatment has been developed, but animals generally recover after 2-5 days of being removed from endophyte-infected pasture and mortality is rare (Mason 1968;Mackintosh et al 1982;Holmes et al 1999;Blythe et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of PRGS have been reported in cattle, sheep, deer, alpaca and horses (Cunningham and Hartley 1959;Mackintosh et al 1982;Holmes et al 1999). Extensive research on PRGS has been performed in ruminants and demonstrates that ingestion of lolitrem B at levels >2 ppm causes signs of neuromuscular dysfunction, which include fine tremors, ataxia, truncal sway, hyperaesthesia, tetany and cerebellar fits, and are intensified by stress or exercise (Cunningham and Hartley 1959;Mackintosh et al 1982;Galey et al 1991;Di Menna et al 1992;Tor-Agbidye et al 2001;Fisher et al 2004;Miyazaki et al 2004;Blythe et al 2007). No effective treatment has been developed, but animals generally recover after 2-5 days of being removed from endophyte-infected pasture and mortality is rare (Mason 1968;Mackintosh et al 1982;Holmes et al 1999;Blythe et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Paxilline and other IDTs were found in moldy tomatoes infected with Penicillium tularense (Andersen and Frisvad 2004). Lolitrem B and epoxy-janthitrem were observed in the fat and milk of growing and lactating animals that grazed on contaminated tall fescue (Miyazaki et al 2004; Finch et al 2012; Finch et al 2013; Shimada et al 2013; Zbib et al 2015). The maximum concentration of these IDTs in cow milk reached 5 ng/ml and 109 ng/ml for lolitrem B and epoxy-janthitrem, respectively (Finch et al 2013).…”
Section: Idts As Threats To Agriculture Public Health and The Fermementioning
confidence: 99%
“…The maximum concentration of these IDTs in cow milk reached 5 ng/ml and 109 ng/ml for lolitrem B and epoxy-janthitrem, respectively (Finch et al 2013). Miyazaki et al (2004) measured 210 ppb lolitrem B in the perirenal fat of Japanese Black cattle feeding on contaminated ryegrass (Miyazaki et al 2004). However, the concentrations of these IDTs decrease rapidly in vivo when the animals are removed from the contaminated pasture, thus reducing the prevalence of food containing these two mycotoxins and limiting the threat to human health (Miyazaki et al 2004; Finch et al 2013).…”
Section: Idts As Threats To Agriculture Public Health and The Fermementioning
confidence: 99%
“…There is no published evidence that demonstrates an accumulation of ergovaline in edible animal tissues in the tall fescue or perennial ryegrass literature. Some studies have clearly demonstrated the presence of lolitrem B and epoxy-janthitrems in lambs (Finch et al 2012) and cattle (Miyazaki et al 2004) adipose tissue. The report by EFSA (2012) suggested a tolerable daily intake of ergot alkaloids at 0.60 mg/kg BW.day.…”
Section: Bioaccumulation and Excretion Of Ergovalinementioning
confidence: 99%